Thermalization dynamics of a gauge theory on a quantum simulator - Zhou, Zhao-Yu; Su, Guo-Xian; Halimeh, Jad C.; Ott, Robert; Sun, Hui; Hauke, Philipp; Yang, Bing; Yuan, Zhen-Sheng; Berges, Jürgen; Pan, Jian-Wei (Science. First release, 2022)
Gauge theories form the foundation of modern physics, with applications ranging from elementary particle physics and early-universe cosmology to condensed matter systems. We perform quantum simulations of the unitary dynamics of a U(1) symmetric gauge field theory and demonstrate emergent irreversible behavior. The highly constrained gauge theory dynamics are encoded in a one-dimensional Bose-Hubbard simulator, which couples fermionic matter fields through dynamical gauge fields. We investigated global quantum quenches and the equilibration to a steady state well approximated by a thermal ensemble. Our work may enable the investigation of elusive phenomena, such as Schwinger pair production and string breaking, and paves the way for simulating more complex, higher-dimensional gauge theories on quantum synthetic matter devices.
Gesehen am 14.11.2022